Primary Versus Secondary Prevention Effects of a Gender-Transformative Sexual Violence Prevention Program Among Male Youth: A Planned Secondary Analysis of a Randomized Clinical Trial - Culyba, Alison J. (Journal of interpersonal violence, 2023)
Engaging adolescent males is a promising violence prevention strategy. This study explored primary versus secondary prevention effects of a gender-transformative program (i.e., Manhood 2.0) versus job-readiness training on multiple forms of violence perpetration. Adolescent males, ages 13 to 19 years, were recruited through youth-serving organizations in Pittsburgh, PA, between July 27, 2015, and June 5, 2017, to participate in an unblinded community-based cluster-randomized trial in 20 neighborhoods. The intervention curriculum, Manhood 2.0, focused on challenging norms that foster gender-based violence and building bystander skills. The control program was job-readiness training. We completed a planned secondary analysis of surveys from baseline and 9 months post intervention (follow-up), wherein we stratified participants based on any sexual violence/adolescent relationship abuse (SV/ARA) at baseline and examined risk of perpetration of SV/ARA, incapacitated sex, sexual harassment, cyber sexual abuse, peer violence, bullying, and homophobic teasing at follow-up. Among 866 participants, mean age was 15.6 years, 70% identified as Black, 6% as Hispanic, and 6% as multiracial. In both the Manhood 2.0 intervention group and job-readiness control groups, youth who reported SV/ARA at baseline were significantly more likely to report any form of SV/ARA, incapacitated sex, sexual harassment, cyber sexual abuse, bullying, and homophobic teasing at follow-up. Among participants who reported no SV/ARA perpetration at baseline, participating in the Manhood 2.0 intervention program was associated with increased risk of SV/ARA at follow-up compared to participating in the job-readiness control program. Among participants who reported SV/ARA perpetration at baseline, participating in the Manhood 2.0 intervention group was associated with lower risk of peer violence at follow-up. Synergizing gender-transformative approaches with job-readiness training may offer opportunities for crosscutting prevention programming to address multiple forms of violence.